Characterization of TIM-3 expression and its prognostic value in patients with surgically resected lung adenocarcinoma. (July 2018) - Su, Hang; Xie, Huikang; Dai, Chenyang; Ren, Yijiu; She, Yunlang; Xu, Long; Chen, Donglai; Xie, Dong; Zhang, Liping; Jiang, Gening; Chen, Chang
Graphical abstract: Highlights: TIM-3 is a highly expressed marker with special clinicopathological features. TIM-3 expression was significantly correlated with PD-1 and CD8 expression. Positive TIM-3 expression was an independent predictor of worse RFS and OS. Combination of TIM-3, PD-1, CD8+ TILs could further stratify patient's prognosis. Abstract: Objectives: T-cell immunoglobulin and mucin-domain containing-3 (TIM-3) is a promising checkpoint. However, its features and prognostic value in lung adenocarcinoma remain undetermined. In this study, we aimed to characterize TIM-3 expression and its prognostic significance in patients with surgically resected lung adenocarcinoma. Materials and methods: Expression of TIM-3 and programmed cell death 1 (PD-1), and density of CD8 + tumor infiltrating lymphocytes (TILs) were evaluated by immunohistochemistry in resected lung adenocarcinoma. The association between clinicopathological features or clinical outcomes and TIM-3 expression was analyzed. Results: A total of 223 patients were enrolled. TIM-3 expression was observed in 107 (48.0%) samples. Positive TIM-3 expression significantly correlated with positive PD-1 expression ( p < 0.001) and high CD8 + TILs density ( p = 0.014). TIM-3 positivity was significantly associated with worse recurrence-free survival (RFS) (hazard ratio [HR], 2.32; 95% confidence interval [CI], 1.44–3.73, p = 0.001) and overall survival (OS) (HR, 2.04; 95% CI, 1.29–3.20, p = 0.002). Subgroup analysis revealed that TIM-3 + /PD-1 + /CD8 low group had the worst RFS (5-year rate: 39.5%, p = 0.002) and OS (5-year rate: 50.0%, p = 0.035), while TIM-3 − /PD-1 − /CD8 high group had the best RFS (5-year rate: 93.8%, p = 0.002) and OS (5-year rate: 100%, p = 0.035). Conclusion: TIM-3 had a relatively high positive expression rate and special clinicopathological features in patients with lung adenocarcinoma. A combination of TIM-3 and/or PD-1 expression or CD8 + TILs density could further stratify patients into different groups with distinct prognosis.